A history of deep time: Indigenous knowledges and deep pasts in settler-colonial presents. Issue 4 (2nd October 2021) - Rademaker, Laura
Abstract: Over the course of the twentieth century, scholars have found diverse ways of reading 'Aboriginal Dreaming' stories as historical accounts of events in Australia's 'deep time'. This article argues that, when analysed alongside developments in Australian settler–Indigenous relations, the various readings of Aboriginal stories map onto changing views of Indigenous difference as well as the usefulness and value of Indigenous culture as a 'deep history' or heritage for the settler nation. This analysis reveals that merely engaging with Indigenous stories is not inherently decolonising. Rather, the interpretation of Aboriginal story is best done with great care and in partnership with Indigenous owners of this knowledge.